2016
DOI: 10.1039/c6ce00079g
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of “L”-shaped V2O5and the improved adsorption capacity by fluorine

Abstract: In this work, V2O5with an interesting “L”-shape is successfully prepared by a simple hydrothermal method without using any surfactant or template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…To study the adsorption mechanism of methyl orange on the prepared porous nanoZnO adsorbent, Langmuir and Freundlich adsorption isotherms models were applied to study the equilibrium adsorption data of methyl orange on the prepared adsorbent, Langmuir adsorption isotherm is based on the assumption that monolayer adsorption occurs on a homogeneous surface; while Freundlich adsorption isotherm is based on the assumption over a heterogeneous surface, the Langmuir and Freundlich isotherms models are according to previous studies [19, 22, 23]. From Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the adsorption mechanism of methyl orange on the prepared porous nanoZnO adsorbent, Langmuir and Freundlich adsorption isotherms models were applied to study the equilibrium adsorption data of methyl orange on the prepared adsorbent, Langmuir adsorption isotherm is based on the assumption that monolayer adsorption occurs on a homogeneous surface; while Freundlich adsorption isotherm is based on the assumption over a heterogeneous surface, the Langmuir and Freundlich isotherms models are according to previous studies [19, 22, 23]. From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From Fig. 6, it can be concluded that the adsorption isotherm of methyl orange can be described well by the Langmuir model rather than Freundlich model ( R 2 was 0.9770 and 0.9319 for Langmuir and Freundlich fit, respectively), which indicates that a monolayer adsorption between the porous nanoZnO and the methyl orange occurs [19, 22].…”
Section: Resultsmentioning
confidence: 99%
“…5 shows the IR spectra of the coatings deposited on substrates heated at various temperatures. At 373 K, the CH and OH bands are clearly identified, as well as the two main bands of V]O and O-V-O [39] at 1005 and 810 cm-1 respectively [40]. The presence of CH bands at low temperatures, even with 5% O 2 in the reactor, indicates that the reaction is not complete in these conditions.…”
Section: Deposition Of V 2 O 5 In An Argon/oxygen Discharge On An Inductively Heated Substratementioning
confidence: 93%
“…194 Doping with metal, non-metal, and rare-earth-doped V 2 O 5 , such as Gd, Nd, Ag, Nb, Ce, Sm, Dy, Mg, Li, W, Sn, Yb, La, and F, affects the E opt of V 2 O 5 with no clear tendency. 108,135,[171][172][173][195][196][197][198][199][200] The E opt increased with increasing Ce-, Sm-, Dy-, and Mgdoped V 2 O 5 , whereas Sn-, Nb-, Gd-, Ag-, and Li-doped V 2 O 5 , lead to a decrease in E opt . For Nd, F, La, Yb, and W doping, E opt changes depending on the dopant concentration.…”
Section: Influence Of Dopantsmentioning
confidence: 99%